Les textiles dans l'intérieur domestique. Étude comparative Perche-Québec, XVIIe-XVIIIe siècles - Mathieu, Jocelyne (Ethnologies, 1983)
AbstractTextiles represent one of three axes of the organization of daily life in its domestic context, the other two being furniture and ustensils. Their significance is no greater than the measure in which they reflect aspects of life styles.Based on post obit inventories from the région of Québec and the Castellany of Mortagne-sur-Perche, the author makes a comparative study of linen, bedding and textile ornamentation in France and Québec in the New France period (1608-1760).